Feasibility Analysis Assistance for Oyster Mushroom Cultivation as a Sustainable Entrepreneurial Solution - Jariah, Ainun; Irdiana, Sukma; Lukiana, Ninik (IMPOWERMENT SOCIETY, 2025)
Oyster mushrooms are widely consumed as part of daily food, similar to green vegetables. They contain beta-glucan fiber, antioxidants, and nutrients that support heart health, immunity, cognitive function, blood sugar control, and reduced cancer risk. These benefits encouraged Mr. Asmari to develop an oyster mushroom processing business. This community service activity evaluates the feasibility of the business based on four main aspects. From the engineering and production aspect, the business location is accessible, and electricity and water are adequate. The mushroom house is suitable, with proper shelves, ventilation, wide access doors, and sufficient lighting. However, production capacity has dropped significantly from about 1 kg to around 100 grams per baglog, indicating reduced productivity. In the aspect of organizational management and human resources, the number of workers is limited, and all production stages depend on minimal labor, so this aspect is considered not feasible. From the market and marketing aspect, products reach several schools and traditional markets, and product innovations match consumer preferences, although the market area remains small. Financial analysis also shows infeasibility, indicated by a payback period of more than five years, negative NPV, an IRR below the 30 percent standard, and a profitability index under 1.